Last glacial maximum glaciers in the Northern Apennines reflect primarily the influence of southerly storm-tracks in the western Mediterranean. (1st October 2018) - Baroni, Carlo; Guidobaldi, Giulia; Salvatore, Maria Cristina; Christl, Marcus; Ivy-Ochs, Susan
Abstract: During the Local Last Glacial Maximum (LLGM), the Northern Apennines hosted more than 100 valley and mountain glaciers covering collectively more than 260 km 2 . Cosmogenic 10 Be exposure ages obtained for the first time along the Apenninic range constrain the age of the LLGM to pre-date ca 21 ka. The estimated volumes of these Late Pleistocene glaciers exceeded 9.1 km 3 w.e. Their reconstructed Equilibrium Line Altitudes (ELAs) range from ca. 1200 m a.s.l. for northerly facing compound basin valley glaciers to ca. 1620 m a.s.l. for southerly facing mountain glaciers. Reconstructed ELAs in the western sector of the Northern Apennines were among the lowest recorded for the whole of the Italian peninsula, including the Alps, and also when compared with other mountain chains in the surrounding Mediterranean basin. These probably reflect exceptionally high accumulation rates fed by storm tracks in the western Mediterranean, which in turn has implications for the atmospheric circulation pattern that prevailed in the region at the time.